Stimulating Housing Markets - BERGER, DAVID; TURNER, NICHOLAS; ZWICK, ERIC (Journal of Finance, 2020)
ABSTRACT We study temporary fiscal stimulus designed to support distressed housing markets by inducing demand from buyers in the private market. Using difference‐in‐differences and regression kink research designs, we find that the First‐Time Homebuyer Credit increased home sales by 490,000 (9.8%), median home prices by $2,400 (1.1%) per standard deviation increase in program exposure, and the transition rate into homeownership by 53%. The policy response did not reverse immediately. Instead, demand comes from several years in the future: induced buyers were three years younger in 2009 than typical first‐time buyers. The program's market‐stabilizing benefits likely exceeded its direct stimulus effects.